2019
DOI: 10.1186/s12913-019-4844-0
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to rethink how we page physicians? Understanding paging patterns in a tertiary care hospital

Abstract: BackgroundFrequent pages can disrupt workflow, interrupt patient care, and may contribute to physician burnout. We hypothesized that paging volumes followed consistent temporal trends, regardless of the medical or surgical service, reflecting systems based issues present in our hospitals.MethodsA retrospective review of the hospital paging systems for 4 services at The Ottawa Hospital was performed. Resident paging data from April 1 to July 31, 2018 were collected for services with a single primary pager numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The on-call otolaryngology service in Calgary, which has the same number of residents as our program, saw an average of six consults per day in 2015 [ 4 ], in comparison to our 15-16 new consults daily. Witherspoon et al looked at pages received by different services at The Ottawa Hospital [ 15 ]. Orthopedic surgery at one campus received an average of 30 pages per day, similar to our 26 pages per 24-hour period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The on-call otolaryngology service in Calgary, which has the same number of residents as our program, saw an average of six consults per day in 2015 [ 4 ], in comparison to our 15-16 new consults daily. Witherspoon et al looked at pages received by different services at The Ottawa Hospital [ 15 ]. Orthopedic surgery at one campus received an average of 30 pages per day, similar to our 26 pages per 24-hour period.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in our study is that the majority (86%) of pages were new consults or direct calls from patients, and 58% led to a new patient encounter. Seventy-five percent of calls in the aforementioned study were from inpatient units [ 15 ], which often represent ward issues regarding active patients. Previous studies have shown that inpatient on-call services receive higher pager volumes during evening hours [ 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and professional demographics (e.g., length of time since degree, length of time in the current setting, etc.). The survey also captured provider ratings on 25 items broadly based on the National Academy of Medicine's system approach to provider burnout ( National Academy of Medicine; Committee on Systems Approaches to Improve Patient Care by Supporting Clinician Well-Being, 2019 ) and included various evidence-based S-T workplace factors (e.g., interruptions and disruptions (e.g., frequent pages or interruptions for non-emergent issues ( Witherspoon et al, 2019 )), work-life integration (e.g., lack of time to exercise, and or engage in enjoyable activities outside of work ( Olson et al, 2014 )), patient-related factors (e.g., difficult interactions with patients and their families ( An et al, 2013 )), organizational culture, technology (e.g., efficiency and usability of EHR and other technologies ( Melnick et al, 2020 )) and communications and relationships within and outside groups). Participants were asked to rate the extent to which they felt the specific workplace factor contributed to burnout, with higher values representing stronger agreement that the factor did contribute to burnout (1 = strongly disagree and 7 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…This leads to increased stress, burnout rates, and frustrations during rounding periods among medical trainees. 3 An algorithm-based text page system for nursing staff would improve communication and rounding efficiency by utilizing a decision tree model. This tree would include the initial decision of page appropriateness during rounding times.…”
mentioning
confidence: 99%